EFFECTIVENESS OF USING ADVANCED PEDEGOGIC TECHNOLOGY METHODS IN TEACHING "GENERAL AND MEDICAL RADIOBIOLOGY" INMEDICAL FIELDS OF HIGHER AND PROFESSIONAL EDUCATIONAL INSTITUTIONS - E. X. Bozorov; F. N. Temirov; M. X. Jalilov; B. N. Burxonov; J. X. Xamroyev; M. N. Ahrorov; X. M. Jalilov (American Journals, 2023)
The article researches the pedagogical skills needed to deepen the knowledge of students of the University of Ibbi. As an object of research, general and medical radiobiology has been studied and the taste ofnew pedagogical technologies developed by qualified teachers in the d ars process has been analyzed. The positive aspects of the use of information communications are shown.